ANALYSIS OF FACTORS AFFECTING THE ECONOMIC SECURITY OF SMALL BUSINESS AND PRIVATE BUSINESS ACTIVITY (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
After small business and private entrepreneurship activity has become the "driver" of the economy in our country, it is more than ever necessary to analyze the comprehensive development of this sector and, most importantly, the principles of its anti-crisis management, as well as the factors affecting its economic security. From this point of view, in this article, factors affecting business activity and its economic security are thoroughly analyzed, and conclusions and suggestions are presented at the end.